1988
DOI: 10.1111/j.1651-2227.1988.tb10861.x
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Drawn From Observing Young Peers Together

Abstract: Based on studies during the past 13 years of what transpires between young peers, lessons are drawn about the nature of human sociability and the development of social skill during the first three years of life. Peer encounters have proven especially helpful for discovering the forms of sociability and social skill the infant is capable of without the aid of a more skillful social partner.From early in infancy, children are quite sociable with peers (age-mates), both in novel play settings and in their own hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
5

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
4
11
0
5
Order By: Relevance
“…This is supported by [14] that proves the influence brought by peers does exist alongside that exerted by the parents.…”
Section: Parental and Peers Influencessupporting
confidence: 64%
“…This is supported by [14] that proves the influence brought by peers does exist alongside that exerted by the parents.…”
Section: Parental and Peers Influencessupporting
confidence: 64%
“…Studies of toddlers interacting with peers highlight the multiple difficulties children have generating coordinated action in the absence of a scaffolding partner until well into the second year of life (eig., Bakeman & Adamson, 1984;Bronson, 1981;Eckerman & Didow, 1988). From early in infancy, young peers are sociable with one another, directing smiles, vocalizations, and gestures to one another, and they influence each other's movements through space and which objects are contacted and manipulated.…”
Section: -24 Monthsmentioning
confidence: 98%
“…Recent research on infants and toddlers together (Eckerman & Didow, 1988) suggests that the observations just reported have captured a natural social capacity readily displayed by kibbutz children because of the intensive social character of their environment. Although infant sociability is viewed äs a natural capacity, it must be distinguished from social competence, which refers to effectiveness with peers through coordinated interactions and reciprocal actions within a relevant affective context.…”
Section: Relations With Peersmentioning
confidence: 99%
“…Although infant sociability is viewed äs a natural capacity, it must be distinguished from social competence, which refers to effectiveness with peers through coordinated interactions and reciprocal actions within a relevant affective context. Early peer encounters have been thought to provide children with the social experience necessary to support the development of social competence (Eckerman & Didow, 1988;Howes, 1988a). Moreover, it has been suggested that peer familiarity facilitates social interaction and the development of specific relationships based on the continued presence of the partner (Doyle, Connolly, & Rivest, 1980;Howes, 1988a).…”
Section: Relations With Peersmentioning
confidence: 99%